4.MOTOR EVOKED POTENTIAL IN PATIENTS WITH PARKINSON’S DISEASE: A TRANSCRANIAL MAGNETIC STIMULATION STUDY (Iraqi Journal of Medical Sciences, 2018)
Background: Parkinson’s disease (PD) is a neurodegenerative condition of the central nervous system, which is accompanied by the impairment of the cortico-subcortical excitation and inhibition systems. It is characterized by motor and non-motor symptoms, having both hypokinetic and hyperkinetic features.Objective: To investigate the integrity of the central motor pathways by studying the motor evoked potential (MEP) latencies, amplitudes and central conduction time (CMCT) of the median nerve in patients with PD as compared to healthy controls.Methods: Twenty-five patients with documented PD were studied; with a mean age of (63.16±5.49 years) as compared to 25 age and sex matched apparently healthy controls. All subjects were instructed about the examination and informed consent was provided. Transcranial magnetic stimulation TMS-MEP study of the right median nerve was done. Cortical and cervical latencies and amplitudes of the MEP study were determined. The responses were recorded with both relaxed and slightly contracted target muscle. CMCT calculation was done by subtraction of the latency of peripheral segment of the motor pathway (spinal motor root to muscle) from that of the entire motor pathway (motor cortex to muscle) or by calculation of the CMCT with the F-wave method. Results: The means of the cortical latencies of PD patients during relaxation and facilitation states were lower than controls; and the differences were significant for both (P=0.03 and 0.02; respectively). In both relaxed and facilitation states, the means of CMCT in PD patients were lower than in control and the difference was significant during contraction (P=0.02), and near statistical significance during relaxation (P=0.08). CMCT calculations by the estimation of F wave and distal motor latency (DML) were equivocal between relaxation and facilitation states. Nevertheless, the differences were not statistically significant (P=0.45; P=0.62; respectively). The means of the MEP amplitude of PD patients were lower than controls (4.21±1.94 versus 4.28± 1.84 mV; respectively). Nevertheless, the differences were not significant (P=0.89).Conclusion: Single-pulse TMS is a valuable study to investigate central motor dysfunction in PD. CMCT measurement of the median nerve or any nerve in the upper limb is a potential marker for the evaluation of the severity of PD; especially in the facilitated state.Keywords: Parkinson’s disease, TMS, MEP, CL, CMCTCitation: Ahmed HR, Al-Hashimi AF. Motor evoked potential in patients with Parkinson’s Disease: a transcranial magnetic stimulation study. Iraqi JMS. 2018; Vol. 16(1): 14-21. doi: 10.22578/IJMS.16.1.4
Keywords: Parkinsons disease; TMS; MEP; CL; CMCT